Labor Dystocia as First Presentation of Pelvic Malignancy - Dennis van Hamont; Petra L. M. Zusterzeel (Case Reports in Obstetrics and Gynecology)
The underlying causes of labor dystocia can be various. Lack of expulsive forces or fetal malpresentation are amongst the most common ones. However, pelvic masses are described as well. Here we describe two cases of labor dystocia as first presentation of pelvic malignancy.